A Cross-Sectional Analysis of Body Composition Among Healthy Elderly From the European NU-AGE Study: Sex and Country Specific Features - Santoro, Aurelia; Bazzocchi, Alberto; Guidarelli, Giulia; Ostan, Rita; Giampieri, Enrico; Mercatelli, Daniele; Scurti, Maria; Berendsen, Agnes; Surala, Olga; Jennings, Amy; Meunier, Nathalie; Caumon, Elodie; et al. (Frontiers in Physiology, 2018)
Body composition (BC) is an emerging important factor for the characterization of metabolic status. The assessment of BC has been studied in various populations and diseases such as obesity, diabetes, endocrine diseases as well as physiological and paraphysiological conditions such as growth and aging processes, and physical training. A gold standard technique for the assessment of human BC at molecular level is represented by dual-energy X-ray absorptiometry (DXA), which is able to precisely assess measure the body mass (and areal bone mineral density-aBMD) on a regional and whole-body basis. For the first time, within the framework of the NU-AGE project, BC has been assessed by means of a whole-body DXA scan in 1121 sex-balanced free-living, apparently healthy older adults aged 65 to 79 years enrolled in 5 European countries (Italy, France, United Kingdom, the Netherlands, and Poland). The aim of this analysis is to provide a complete profile of BC in healthy elderly participants from five European countries and to investigate country- and sex-related differences by state-of-the-art DXA technology. To compare BC data collected in different centers, specific indexes and ratios have been used. Non-parametric statistical tests showed sex-specific significant differences in certain BC parameters. In particular, women have higher fat mass (Fat/Lean mass ratio: by 67%, p<2.2e-16) and lower lean mass (Lean Mass Index: by -18%, p<2.2e-16) than men. On the other hand, men have higher android fat mass than women (Android/gynoid Fat Mass ratio: by 56%, p<2.2e-16). Interesting differences also emerged among countries. Polish elderly have higher fat mass (Fat/Lean mass ratio: by 52%, p<2.2e-16) and lower lean mass (Skeletal Mass index: by -23%, p<2.2e-16) than elderly from the other four countries. At variance, French elderly show lower fat mass (Fat/Lean mass ratio: by -34%, p<2.2e-16) and higher lean mass (Skeletal Mass index: by 18%, p<2.2e-16). Moreover, five BC profiles in women and six in men have been identified by a cluster analysis based on BC parameters. Finally, these data can serve as reference for normative average and variability of BC in the elderly populations across Europe.